Unfinished business : faith communities and reconciliation in a post TRC context - Hansen, Len (Sun Media, 2020)
"This publication takes one back to the Truth and Reconciliation Commission's (TRC) Faith Communities' Hearings in 1997 and the re-enactment of those hearings in 2014. Some communities revisit their support of those in power and their change of heart. Others revisit their struggle against the regime and its ideology. All also revisit promises made in 1997 to work together, individually and collectively, toward a new society post 1994. After twenty years, the same faith communities (and some additional ones) and some prominent South Africans who played leading roles in the run-up to and during the hearings ask what faith communities promised at the time and whether this has been achieved by 2014. Over two days, together with local and international observers, they again face the past, but also the unfinished business in the present and future of a just, reconciled and transformed South Africa so clearly envisioned by the TRC, in 1997."--Publisher.